Physical exercise and sex steroid hormones in breast cancer - Silvia Rocha-Rodrigues (Termedia Publishing House, 2020)
Cumulative epidemiological evidence demonstrates that regular physical exercise is one of the most powerful lifestyle strategies used to mitigate the risk of developing breast cancer (BrC) and disease recurrence. The physical exercise recommendations for BrC survivors follow the general physical activity guidelines, 150 min of moderate-intensity exercise or 75 min of vigorous aerobic activity per week. However, to better understand the mechanisms underlying the positive effects of physical exercise is very important to prescribe and implement the most optimal training routine in BrC survivors. As far as we know, sex steroid hormonal response is one of the mechanisms why physical exercise exerts their effects with additional impact on systemic levels of cancer risk factors. Here, we review the evidence of the physical-exercise-mediated alterations in sex steroid hormones and additionally their ability to prevent or attenuate skeletal toxicities of induced by BrC, providing an overview of the effects of physical exercise on the BrC-related underlying mechanisms.